Kontribusi Masyarakat Muslim Terhadap Kegiatan Keagamaan Di Desa Lahei Mangkutup - Bahraini, Nurul; Muliansyah, Ainol; Minal Janah, Anisa (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The aim of this research is to study and find out how much community participation is in religious activities carried out in Lahei Mangkutup Village. The method used in conducting this research was qualitative. The approach taken was phenomenology. The results of research conducted by KKN IAIN Palangka Raya students found that the community still has minimal awareness of participation in religious activities. One example that can be used as a benchmark is when students carry out activities regarding providing material and practice regarding fardhu kifayah. The local community has been given an announcement about carry out these activities both orally and in writing. Despite this, the community is still not aware and willing to attend these activities. The author provides solutions (1) During yasinan activities, mothers are expected for the mosque members who lead the activities to take the time to provide da'wah or kultum about our rights and obligations as Muslims. (2) Providing a forum or place to share religious matters. (3) Instilling the value of assertiveness and giving the village community a mandate for religious activities.